Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 157790 by MathSh last updated on 28/Oct/21

Answered by MJS_new last updated on 28/Oct/21

let c=cos x  ((32c^5 −40c^3 +9c))^(1/3) +((16c^5 −20c^3 +4c))^(1/3) =(c)^(1/3)   u+v=w     ∣^3   u^3 +3u^2 v+3uv^2 +v^3 =w^3   u^3 +3uv(u+v)+v^3 =w^3   u^3 +3uvw+v^3 =w^3   3uvw=w^3 −(u^3 +v^3 )  27u^3 v^3 w^3 =(w^3 −(u^3 +v^3 ))^3   inserting we get  108c^3 (4c^4 −5c^2 +1)(32c^4 −40c^2 +9)=−1728c^3 (4c^4 −5c^2 +1)^3   ⇒ c=0∨4c^4 −5c^2 +1=0  32c^4 −40c^2 +9=−16(4c^4 −5c^2 +1)^2   let c^2 =d+(5/8)  32d^2 −(7/2)=−(((64d^2 −9)^2 )/(16))  d^4 −(5/(32))d^2 +((25)/(4096))=0  (d^2 −(5/(64)))^2 =0  d=±((√5)/8)  c^2 =((5±(√5))/8)  now we have  c=0  c=±1  c=±(1/2)  c=±(√((5−(√5))/8))  c=±(√((5+(√5))/8))  testing leads to  c=0∨c=±(1/2)∨c=±1  for 0≤x<2π we get  x∈{0, 2, 3, 4, 6, 8, 9, 10}×(π/6)

$$\mathrm{let}\:{c}=\mathrm{cos}\:{x} \\ $$$$\sqrt[{\mathrm{3}}]{\mathrm{32}{c}^{\mathrm{5}} −\mathrm{40}{c}^{\mathrm{3}} +\mathrm{9}{c}}+\sqrt[{\mathrm{3}}]{\mathrm{16}{c}^{\mathrm{5}} −\mathrm{20}{c}^{\mathrm{3}} +\mathrm{4}{c}}=\sqrt[{\mathrm{3}}]{{c}} \\ $$$${u}+{v}={w}\:\:\:\:\:\mid^{\mathrm{3}} \\ $$$${u}^{\mathrm{3}} +\mathrm{3}{u}^{\mathrm{2}} {v}+\mathrm{3}{uv}^{\mathrm{2}} +{v}^{\mathrm{3}} ={w}^{\mathrm{3}} \\ $$$${u}^{\mathrm{3}} +\mathrm{3}{uv}\left({u}+{v}\right)+{v}^{\mathrm{3}} ={w}^{\mathrm{3}} \\ $$$${u}^{\mathrm{3}} +\mathrm{3}{uvw}+{v}^{\mathrm{3}} ={w}^{\mathrm{3}} \\ $$$$\mathrm{3}{uvw}={w}^{\mathrm{3}} −\left({u}^{\mathrm{3}} +{v}^{\mathrm{3}} \right) \\ $$$$\mathrm{27}{u}^{\mathrm{3}} {v}^{\mathrm{3}} {w}^{\mathrm{3}} =\left({w}^{\mathrm{3}} −\left({u}^{\mathrm{3}} +{v}^{\mathrm{3}} \right)\right)^{\mathrm{3}} \\ $$$$\mathrm{inserting}\:\mathrm{we}\:\mathrm{get} \\ $$$$\mathrm{108}{c}^{\mathrm{3}} \left(\mathrm{4}{c}^{\mathrm{4}} −\mathrm{5}{c}^{\mathrm{2}} +\mathrm{1}\right)\left(\mathrm{32}{c}^{\mathrm{4}} −\mathrm{40}{c}^{\mathrm{2}} +\mathrm{9}\right)=−\mathrm{1728}{c}^{\mathrm{3}} \left(\mathrm{4}{c}^{\mathrm{4}} −\mathrm{5}{c}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{3}} \\ $$$$\Rightarrow\:{c}=\mathrm{0}\vee\mathrm{4}{c}^{\mathrm{4}} −\mathrm{5}{c}^{\mathrm{2}} +\mathrm{1}=\mathrm{0} \\ $$$$\mathrm{32}{c}^{\mathrm{4}} −\mathrm{40}{c}^{\mathrm{2}} +\mathrm{9}=−\mathrm{16}\left(\mathrm{4}{c}^{\mathrm{4}} −\mathrm{5}{c}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} \\ $$$$\mathrm{let}\:{c}^{\mathrm{2}} ={d}+\frac{\mathrm{5}}{\mathrm{8}} \\ $$$$\mathrm{32}{d}^{\mathrm{2}} −\frac{\mathrm{7}}{\mathrm{2}}=−\frac{\left(\mathrm{64}{d}^{\mathrm{2}} −\mathrm{9}\right)^{\mathrm{2}} }{\mathrm{16}} \\ $$$${d}^{\mathrm{4}} −\frac{\mathrm{5}}{\mathrm{32}}{d}^{\mathrm{2}} +\frac{\mathrm{25}}{\mathrm{4096}}=\mathrm{0} \\ $$$$\left({d}^{\mathrm{2}} −\frac{\mathrm{5}}{\mathrm{64}}\right)^{\mathrm{2}} =\mathrm{0} \\ $$$${d}=\pm\frac{\sqrt{\mathrm{5}}}{\mathrm{8}} \\ $$$${c}^{\mathrm{2}} =\frac{\mathrm{5}\pm\sqrt{\mathrm{5}}}{\mathrm{8}} \\ $$$$\mathrm{now}\:\mathrm{we}\:\mathrm{have} \\ $$$${c}=\mathrm{0} \\ $$$${c}=\pm\mathrm{1} \\ $$$${c}=\pm\frac{\mathrm{1}}{\mathrm{2}} \\ $$$${c}=\pm\sqrt{\frac{\mathrm{5}−\sqrt{\mathrm{5}}}{\mathrm{8}}} \\ $$$${c}=\pm\sqrt{\frac{\mathrm{5}+\sqrt{\mathrm{5}}}{\mathrm{8}}} \\ $$$$\mathrm{testing}\:\mathrm{leads}\:\mathrm{to} \\ $$$${c}=\mathrm{0}\vee{c}=\pm\frac{\mathrm{1}}{\mathrm{2}}\vee{c}=\pm\mathrm{1} \\ $$$$\mathrm{for}\:\mathrm{0}\leqslant{x}<\mathrm{2}\pi\:\mathrm{we}\:\mathrm{get} \\ $$$${x}\in\left\{\mathrm{0},\:\mathrm{2},\:\mathrm{3},\:\mathrm{4},\:\mathrm{6},\:\mathrm{8},\:\mathrm{9},\:\mathrm{10}\right\}×\frac{\pi}{\mathrm{6}} \\ $$

Commented by MathSh last updated on 28/Oct/21

Perfect dear Ser, thank you very much

$$\mathrm{Perfect}\:\mathrm{dear}\:\boldsymbol{\mathrm{Ser}},\:\mathrm{thank}\:\mathrm{you}\:\mathrm{very}\:\mathrm{much} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com